Rhythm of tantrums - Sravanti, L.; Karki, U.; Seshadari, S. (Journal of Psychiatrists’ Association of Nepal, 2018)
Temper tantrums are part of the normal course of development occurring most commonly in toddlers. There is a chance that these tantrums can become pathological, more so in case of dysfunctional family dynamics. And as it happens in the context of family, it can become a “family problem” as well. Early identification of abnormal tantrum behaviour and interventions directed to help parents handle these tantrums can prevent their long-term adverse consequences. The focus of this article is on why temper tantrums occur, what elements constitute a tantrum, stages through which they progress and simple methods of handling tantrums. It is done with the help of an example and some illustrations that can be useful in psychoeducation to families about tantrum behaviour.